ECOTOURISM DEVELOPMENT IN SUNGAI JANIAH, AGAM: THE PARADIGMS FROM THE LOCAL COMMUNITY - Hendri Azwar; Pasaribu Pasaribu; Heru Pramudia (Institut Pariwisata dan Bisnis Internasional, 2019)
Ecotourism pays attention to conserved ecosystems with the aim of improving the welfare of local communities. Ecotourism development might have a positive impact on the natural, economic, social and cultural environment. Sungai Janiah is one of the tourist destinations in Agam Regency which has its own attraction that has the potential to become ecotourism. To support this, full support from the local community as a tourism agent is needed later. The purpose of this study is to identify and analyze local community surveys about ecotourism in the Sungai Janiah. This type of research is a quantitative descriptive study with survey methods. The research sample of 77 respondents were taken by purposive sampling technique by distributing questionnaires to families who settled in the Sungai Janiah. The data analysis technique used is descriptive analysis using score classification. The results showed 86% of the public strongly agreed that the Sungai Janiah would become ecotourism. Furthermore, in terms of environmental dimension, 89.61% of the respondents stated strongly agree, the Economic dimension 98.70% of the respondents strongly agreed, the cultural dimension 96.10% of the respondents strongly agreed, and the Social dimension 72.73% the respondents strongly agreed. From the results of the community survey, it is generally apparent that the community strongly agrees that the concept of ecotourism is suitable to be developed in the Sungai Janiah.